Quran reading class system for Fadilah's Quran Centre / Muhammad Muizzudin Mustaza - Mustaza, Muhammad Muizzudin (2016)
The purpose of Quran Reading Class system implemented was to help the staff of Fadilah's Quran Reading Centre in managing their attendance and reading progress system. First of all, the staff or parents will register their parents and their kids who going to attend the class name inside the system. Then the staff will manage the attendance of the kids monthly. The number of days the children attend, absent, sick and other reason they did not attend the class are calculated monthly. As for the reading progress, the staff will insert the details regarding what book, surah, sentence, and page did the student reads. The information of the both attendance and reading progress can be view by every parents if and only if they registered inside the system.